2021
DOI: 10.1177/1120672121992680
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of topical tacrolimus 0.03% versus cyclosporine 0.05% in the treatment of dry eye secondary to Sjogren syndrome

Abstract: Purpose: To compare the effect of topical application of tacrolimus 0.03% eyedrops versus cyclosporine 0.05% in Sjogren syndrome subjects with severe dry eyes. Design: A prospective single-blinded simply randomized controlled study. Methodology: 60 Sjogren patients were randomized into Group A: 30 patients were instructed to put tacrolimus 0.03% eyedrops in one eye for 6 months and placebo eyedrops in the other eye, ( N = 30, 44.9 ± 12.58 years). Group B: 30 patients were instructed to put cyclosporine 0.05% e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…Anesthetized animals (2.5% (v/v) isoflurane/oxygen) were positioned into the imaging bed, monitoring the respiration frequency. Afterward, 7.5 µL of each tacrolimus formulation, previously radiolabeled with 18 F-fluorodeoxyglucose ( 18 F-FDG), was instilled into the conjunctival sac of both eyes using a micropipette. The administered radioactivity was 0.20-0.25 MBq per eye.…”
Section: In Vivo Evaluation Of the Residence Time On The Ocular Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…Anesthetized animals (2.5% (v/v) isoflurane/oxygen) were positioned into the imaging bed, monitoring the respiration frequency. Afterward, 7.5 µL of each tacrolimus formulation, previously radiolabeled with 18 F-fluorodeoxyglucose ( 18 F-FDG), was instilled into the conjunctival sac of both eyes using a micropipette. The administered radioactivity was 0.20-0.25 MBq per eye.…”
Section: In Vivo Evaluation Of the Residence Time On The Ocular Surfacementioning
confidence: 99%
“…Tacrolimus is a macrolide with a high molecular weight (804.02 g/mol) isolated from Streptomyces tsukubaensis, with a great immunosuppressive activity (100 times more potent than cyclosporine A) [10,11] that inhibits T cell proliferation and suppresses the release of inflammatory cytokines; it can theoretically be used to reduce inflammatory activity in uveitis patients [3]. This drug has been used in different ocular diseases including corneal graft rejection [12][13][14], vernal keratoconjunctivitis (VKC) [15][16][17], dry eye [11,18], uveitis [5,19,20], scleritis [21,22] or graft-versus-host disease [23][24][25], among others. Additionally, clinical studies have shown tacrolimus' high effectivity compared to other immunosuppressants such as cyclosporine, at lower concentrations [26].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, TAC is commercially available in oral and intravenous formulations, used in transplanted patients, and as an ointment for the treatment of atopic dermatitis [ 47 ]. TAC eyedrops can constitute an alternative in the treatment of uveitis [ 48 , 49 ] because it has been successfully used for various immune-mediated ocular disorders such as graft rejection [ 20 ], vernal keratoconjunctivitis (VKC) [ 21 , 22 , 23 , 24 ], dry eye [ 25 ] or scleritis [ 26 , 27 ]. However, TAC eyedrops are not marketed and they must be elaborated in HPDs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, when patients do not respond to this therapy or have a contraindication for the use of corticosteroids, it is necessary to resort to ophthalmic topical immunosuppressants in order to achieve a sustained control of the inflammatory process [ 17 , 19 ]. In this context, the use of topical tacrolimus (TAC) could be an alternative which has already demonstrated safety and effectiveness in other ocular pathologies including corneal graft rejection [ 20 ], vernal keratoconjunctivitis (VKC) [ 21 , 22 , 23 , 24 ], dry eye [ 25 ] or scleritis [ 26 , 27 ] among others.…”
Section: Introductionmentioning
confidence: 99%
“…Only more recently has its efficacy been explored in clinical trials and experimental studies and found to improve the status of the ocular surface in patients with Sjögren's syndrome–related DED. 5 , 6 …”
Section: Introductionmentioning
confidence: 99%